Data management technologies and applications : 6th International Conference, DATA 2017, Madrid, Spain, July 24-26, 2017, Revised selected papers /: 6th International Conference, DATA 2017, Madrid, Spain, July 24-26, 2017, Revised selected papers. (2018) - Unknown
No abstract available